Fundamentos constitucionais da desjudicialização e limitação do acesso do Estado ao poder judiciário - Laranja, Anselmo Laghi (2018)
This thesis is the result of the study and research upheld in the Stricto Sensu Postgraduate Program of the “Faculdade de Direito de Vitória” (FDV), more specifically, following the research guideline "Democracy, Citizenship and Fundamental Rights". Its objective is to respond the question: what are the constitutionally adequate grounds for limiting the access of legal entities ruled by public law (State) to the Judiciary in the context of systemic sluggishness? Bearing that in mind, the Law Structuring Theory by Friedrich Müller's is established as a theoretical and methodical basis, from which its main characteristics are explained. Hypotheses on the normative program of the fundamental right of access to justice are formulated based on the elements of strictore sensu actualization (grammatical, systematic, historical, genetic and teleological interpretation) based on the linguistic data extracted from art. 5th inc. XXXV of the Federal Constitution and art. 25 of the American Convention of Human Rights, as well as other correlated normative provisions in a secondary way. The normative scope of the crisis of the Judiciary Power is understood as a consequence of the systemic sluggishness, and the influence of the behavior of legal entities of public law in this context is assessed. A fallibility test on the hypotheses of the normative program is carried out based on the analysis of the entire content of the previous 65 precedents judged by the Federal Supreme Court between 1988 and 2015, and specific parameters to use the fundamental right of access to justice based on them are searched. The hypotheses of the normative program are linked, the parameters of use of the right of access to justice are assessed by the jurisprudence of the Supreme Court, the data from the normative scope of systemic sluggishness and State participation are checked, in order to verify the constitutionally adequate grounds that could be used to assist in the actualization of the fundamental right of access to justice by the reduction of litigation abuse and limitation of the State's access to the Judiciary.